A Framework for Assessing Systemic Risk - Dijkman, Miquel (2012)
When faced with financial crises, authorities worldwide tend to respond aggressively with public support measures. Given the adverse impact on moral hazard and market discipline, support measures involving public money are ideally limited to crisis situations involving systemic risk: a disturbance in the financial system that is serious enough to affect the real economy. This note sets out the main characteristics of a systemic risk assessment framework: a simple analytical framework that can be used by authorities with financial crisis management responsibilities in times of financial crisis to assess the extent to which that particular crisis situation poses systemic risk.